TECHNICAL ANALYSIS OF ENGINE PROPELLER MATCHING KRI X AFTER MAIN ENGINE REPOWERING - Fajar, Imron Achmadi; Ratna, Miftakhul Jannah Dwi (Department of Marine Engineering, Universitas Hang Tuah, 2024)
The gas turbine which is one of the main engines of KRI X is not used anymore because of the amount of damaged material. In 2017 it was decided to replace its main engine. Ships that previously used gas turbines and two diesels as the main engine are replaced with four MTU diesel brands with 4000 HP power and 2100 rpm rotation per engine. With a fixed propeller and a power change on the main engine, the matching point of the main engine also changes. Referring to the problem, this study conducted an assessment of engine propeller matching obtained after repowering the main engine, by calculating the pricing of the ship and calculating the power required by the ship. The calculation of ship resistance is done in two ways that is with the help of running software maxsurf with the Holtrop method and calculation by using an empirical formula. Having known the price of the ship's resistance and power required, then calculated the speed of the ship with the new main engine and the variation of the pitch propeller. The result of this research obtained the operating point (matching point) which resulted in optimum speed obtained at the main rotation condition of 1974 rpm, propeller rotation 452,666 rpm, with 85% power loading that is 6152,426 kW, ship speed reached 17,855 Knot, and in this condition is deemed to be by the operation of the continuous service rating.